Genome Comparison Reveals Mutation Hotspots in the Chloroplast Genome and Phylogenetic Relationships of Ormosia Species. (21st August 2019) - Liu, Hongshan; Su, Zhihai; Yu, Shuiqing; Liu, Jialin; Yin, Xiaojuan; Zhang, Guowei; Liu, Wei; Li, Bin
Abstract : The papilionoid legume genus Ormosia comprises approximately 130 species, which are distributed mostly in the Neotropics, with some species in eastern Asia and northeastern Australia. The taxonomy and evolutionary history remain unclear due to the lack of a robust species-level phylogeny. Chloroplast genomes can provide important information for phylogenetic and population genetic studies. In this study, we determined the complete chloroplast genome sequences of five Ormosia species by Illumina sequencing. The Ormosia chloroplast genomes displayed the typical quadripartite structure of angiosperms, which consisted of a pair of inverted regions separated by a large single-copy region and a small single-copy region. The location and distribution of repeat sequences and microsatellites were determined. Comparative analyses highlighted a wide spectrum of variation, with trnK-rbcL, atpE-trnS-rps4, trnC-petN, trnS-psbZ-trnG, trnP-psaJ-rpl33, and clpP intron being the most variable regions. Phylogenetic analysis revealed that Ormosia is in the Papilionoideae clade and is sister to the Lupinus clade. Overall, this study, which provides Ormosia chloroplast genomic resources and a comparative analysis of Ormosia chloroplast genomes, will be beneficial for the evolutionary study and phylogenetic reconstruction of the genus Ormosia and molecular barcoding in population genetics and will provide insight into the chloroplast genome evolution of legumes.